METODE DAKWAH GUS DUR DAN ERA REVOLUSI INDUSTRI 4.0 - Faizatun Khasanah (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
Da'wa in the era of the industrial revolution 4.0 experienced significant development. This can be seen from the rise of da’wa on Youtube, Instagram, Twitter, Facebook, and other social media platform. In the other hand, today's da'wa faces challenges such as the degradation of the preaching message content. As a preacher in his time, Gus Dur had an important method of preaching to be explored and replicated. Gus Dur's da'wa who shared peace and pluralism became a special characteristic. This study wants to answer question of how the Gus Dur da’wa method and its relevance to the era of the industrial revolution 4.0. This research used a literature study approach. This research found three methods of Gus Dur’s preaching. First, the written preaching. Second, the verbal preaching. Third, preaching in action. The three methods are relevant to use in the era of industrial revolution 4.0 which characterized the massive use of digital lines to preach.